The effectiveness of the use of funds in Capital Projects: Case study of Eskom a hedging perspective - Jezi, Priscilla (Graduate School of Business (GSB), 2019)
Eskom is currently one of the biggest importers of goods and services in the country. Companies exposed to foreign exchange rate risk should hedge as a mitigation strategy. Eskom hedges all commitments above R150 000 according to their policy. The most common hedging instrument that is used is forward exchange contract (FEC) and swaps. This thesis investigates how the efficient use of funds by using right tools could reduce capital costs for Eskom capital projects. This study will explore how much Eskom has been able to apply hedging instruments and strategies to improve its capital utilisation efficiency. This study also sets out to ascertain the factors that may have negative implications on the performance of the hedging strategies applied to the management of transactions such as pre take up, cancellation and renewal of covers. Timing was identified as one of the main factors and a key cost driver in these transactions which has a destabilising effect on corporate hedging strategies and performance if it is not managed well. This study investigates its effects and the implications thereof and investigates the timing of taking the cover as well as timing for roll-overs or renewal, pre-take ups and cancellations. Correct hedging strategies like taking the opposite forward contract can be applied when currency is no longer needed at maturity to offset or minimise the impact. Such strategies are more efficient when applied timeously than towards expiry of the cover. Timeous communication from cross-functional teams on any change is therefore vital in order to ensure that a company’s portfolio management reflects the interdisciplinary approach between strategic, operational and financial dimensions. Based on the findings, the research recommends enhanced monitoring of forex processes against operational processes, amongst other things. Financial hedging strategies are complementary to operational hedging strategies. There is more value in financial hedging strategies when used together with operational hedging strategies as both strategies contribute towards achieving the same goal of reducing costs on capital projects and increasing shareholder value.